Psychoeducation for Parents Through a News Website on the Dangers of Artificial Intelligence Dependence Among Students - Miqdad Daly Ahmad; Rahmita Laily Muhtadini; Diah Liandary Nurmaulida - (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The use of Artificial Intelligence (AI) is becoming increasingly widespread among students, particularly in the completion of school assignments. However, excessive dependence on AI may reduce critical thinking skills, creativity, and learning independence. This community service program aims to provide psychoeducation to parents about the dangers of AI dependence among students through an online news platform. The method employed was a one-group pretest–posttest design involving 10 parents. The psychoeducation program was delivered through articles published on the Opini Harian Bhirawa news website. The results indicate that the psychoeducational method effectively enhanced parents’ understanding of the negative impacts of excessive AI use. The use of a website-based psychoeducation method also proved to be accessible and efficient for information dissemination. However, the absence of direct interaction limits emotional engagem ent & deeper comprehension. This program recommends combining online approaches with direct interactions through webinars or interactive discussions to achieve more effective outcomes.